Resistin: A reappraisal. (March 2019) - Acquarone, E.; Monacelli, F.; Borghi, R.; Nencioni, A.; Odetti, P.
Highlights: Several adipokines, including resistin, play a key role in the aging process. Resistin is associated with the onset of age-related chronic diseases. Resistin is a molecular link between biological aging and frailty. Resistin modulates metabolism and inflammation during aging. Abstract: From a biological point of view, aging can be considered a progressive inability of an organism to react to stress, maintain homeostasis, and survive unfavourable changes during post-maturational life. The expression of several adipokines changes during aging and for some changes, a role in the onset of chronic disease and frailty has been proposed. Among adipokines, resistin was shown in recent studies to play a key role in aging. Resistin is a small secreted protein that regulates glucose metabolism in mammalians. High resistin levels induce insulin resistance and exert proinflammatory effects. Consistently, resistin has been shown to play a pivotal role in various metabolic, inflammatory, and autoimmune diseases. Herein, the role of resistin as a molecular link between aging and age-related conditions was reviewed and the clinical implications of this knowledge discussed.